The quality of home runs : the passion, politics, and language of Cuban baseball - Carter, Thomas F., 1967- (Duke backfile, 2008)
Uses the sport of baseball, about which most Cubans are passionate, to look at what it means to be Cuban and at how Cuba deals with the outside world, as well as to compare various disciplinary approaches to the sport.